Technological Innovations in Tropical Livestock Development for Environmental Sustainability and Food Security: Proceedings of the 4th International Conference on Improving Tropical Animal Production for Food Security (ITAPS 2023), 4–5 December 2023, Kendari, Indonesia - Purnaning Dhian Isnaeni; Mashitah Shikh Maidin; Muhammad Amrullah Pagala; Widhi Kurniawan; asma bio Kimestri (CRC Press, 2024)
This book contains the proceedings of the fourth International Conference on Tropical Animal Production for Food Security (ITAPS) exploring Technological Innovations in Tropical Livestock Development for Environmental Sustainability and Food Security. It discusses two interconnected issues: tropical livestock farming and environmental concerns, while addressing the adoption of innovative technologies and sustainable farming practices as a crucial step in addressing challenges related to tropical livestock farming. The contents of the proceedings include the latest research that can be applied in agricultural fields to improve the agriculture business, including topics such as: Leveraging environmentally friendly technologies to enhance production efficiency, manage waste effectively, and reduce carbon footprints Halal meat production in the modern era Availability of animal waste resources as alternative energy The book will be valuable to students, researchers, and professionals in the agricultural fields and science.
Keywords: 630; Food technology; Animal production; Animal product technology; Agribusiness; Animal health